PENGARUH LATIHAN SHOULDER PRESS TERHADAP KETEPATAN LOB DALAM PERMAINAN BULUTANGKIS PADA SISWA PUTRA SMPN 1 LABUAPI - Balkis Ratu NL Esser; Indri Susilawati (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2020)
Based on the initial observations at SMPN 1 Labuapi, some of students physical strength has not been maximal in performing accuracy Lob which has an impact on low badminton achievement. However, to almost all sports concept, especially badminton game of each physical component is needed, so the priority of emphasis depends on the dominant characteristics of the sport that is fostered. Based on the explanation, the problem can be formulated, such as Is there any influence of shoulder press exercises on The Accuracy of Lob in badminton games for VIII grade students of SMPN 1 Labuapi Period 2019/2020?. Based on the problems that have been found, the purpose of this study was wanted to know the influence of shoulder press exercises on The Accuracy of Lob in badminton games for VIII grade students of SMPN 1 Labuapi. This research design was using experimental. In this research, the data collection method used is the action test, documentation and observation method. In this study, the subjects that used as a population were all students of VIII grade SMPN 1 Labuapi Period 2019/2020 which amounts to 115 people. Sampling technique used is Random Sampling technique that is sampling by group. The number of samples taken was 20% x 115 as for 23 students. Data analysis techniques was used statistical analysis using One Group Pretest-Posttest Design. From the results of data analysis and research observations during this research was carried out, and the calculations and statistics, it can be concluded that the t-count of 6,564 > t-table of 2,074 at the level of significance of 5%. In other words, the final results were very significant testing, so as a conclusion that "There is an influence of shoulder press exercises on The Accuracy of Lob in badminton games for VIII grade students of SMPN 1 Labuapi Period 2019/2020" was accepted